The Impact of E-Learning-Based Training, Work Motivation, and Discipline on Employee Competence at KPP Pratama Pematang Siantar - Gabe Simorangkir, Indra; Sahyar, Sahyar; Daulay, Pardamean (Universitas Yudharta Pasuruan, 2023)
English Version The purpose of this study was to investigate the impact of e-learning-based training, work motivation, and work discipline on employee competency at KPP Pratama Pematang Siantar. This study employs descriptive analysis and multiple linear regression analysis with SPSS for data processing. The research sample was made up of 96 employees drawn from 111 different groups using purposive sampling. Employee competency can be explained by 58.2% of the factors e-learning-based training, work motivation, and work discipline. The remaining 41.8% is influenced by issues outside the scope of this study. Regression analysis results show that partially e-learning-based training, work motivation, and work discipline all have a significant and beneficial impact on employee competence, with e-learning-based training having a bigger impact than work motivation and work discipline. Versi Indonesia Tujuan riset ini menganalisa akibat pelatihan berbasis platform elearning, motivasi kerja serta disiplin kerja terhadap kompetensi karyawan di KPP Pratama Pematang Siantar. Riset ini memakai analisis regresi linear berganda dengan memakai program SPSS. Sampel riset sebesar 96 karyawan dari 111 populasi dengan memakai metode sampling purposive sampling. Hasil penelitian menunjukkan bahwa pelatihan berbasis e-learning, motivasi dan disiplin kerja dapat meningkatkan kompetensi karyawan sebesar 58,2% sebaliknya lebihnya 41, 8% dipengaruhi oleh aspek lain yang tidak dimasukkan dalam riset ini. Hasil analisis regresi secara parsial menunjukkan bahwa pelatihan berbasis platform e- learning, motivasi dan disiplin kerja mempengaruhi secara positif signifikan kepada kompetensi karyawan.